Exact optical solutions for the regularized long-wave Kadomtsev-Petviashvili equation. (16th September 2020) - Ghanbari, Behzad; Günerhan, Hatíra; Momani, Shaher
Abstract: Exploring new wave soliton solutions to nonlinear partial differential equations has always been one of the most challenging topics in different disciplines of physics, applied mathematics, and engineering. In this paper, we examine the regularized long-wave Kadomtsev-Petviashvili (KP) equation using the generalized exponential rational function method (GERFM). Through the application of this method, fourteen explicit traveling wave solutions are formally generated. Furthermore, some graphical representations of the acquired solutions are also included to indicate that all parameters can drastically influence their nature, profile, and structures. The method employed in this paper is very simple and straightforward to use and at the same time with much lower computational costs compared to other known methods in the field. So, it can be considered direct and powerful mathematical tools to derive exact soliton wave solutions of other nonlinear models. All symbolic manipulations are done in Mathematica software.